Execution Delay and Its Impact on the Psychological Suffering of Death Row Inmates in the Indonesian Criminal Law System - Padlillah, Padlillah; Heriyanto, Heri (West Science Law and Human Rights, 2025)
This study analyzes the issue of execution delays and their impact on the psychological suffering of death row inmates in Indonesia's criminal law system. Using a normative juridical approach, the research identifies a significant normative gap, as Indonesian positive law lacks explicit regulations governing the time limit for carrying out executions after a verdict becomes final. This legal vacuum leads to prolonged uncertainty for inmates, resulting in extreme psychological distress known as the death row phenomenon. This condition is argued to constitute cruel, inhuman, or degrading treatment, violating both international human rights principles, such as those in the ICCPR, and Indonesia's constitutional guarantees of humane treatment and legal certainty. The analysis reveals a fundamental tension between retributive justice and substantive humanity. The study concludes by emphasizing the urgent need for legal reform to establish clear execution time limits and robust oversight mechanisms. This is crucial to align Indonesia's penal system with the principles of substantive justice, human dignity, and the rule of law.